A validated HPLC-MS/MS method for the simultaneous determination of ecdysteroid hormones in subminimal amounts of biological material - Marešová, Lucie; Moos, Martin; Opekar, Stanislav; Kazek, Michalina; Eichler, Clemens; Šimek, Petr (Journal of lipid research, 2024)
Ecdysteroids represent a large class of polyhydroxylated steroids which, due to their anabolic properties, are marketed as dietary supplements. Some ecdysteroids also act as important hormones in arthropods, where they regulate molting, development, and reproduction and many of these insects are miniature organisms that contain submicroliter levels of circulating biofluids. Analysis of ecdysteroids is further complicated by their very low abundance, large fluctuations during development, and difficult access to a pooled sample, which is important for quantitative measurements. In this work, we propose a new method that overcomes the described difficulties and allows validated quantification of four ecdysteroids in minimal amounts of biological material. After methanolic extraction, detectability of the ecdysteroids is increased 16- to 20-fold by conversion to their 14,15-anhydrooximes. These are further purified by pipette tip solid-phase extraction on a three-layer sorbent and subjected to HPLC-MS/MS analysis. Full validation was achieved using hemolymph from larvae of the firebug Pyrrhocoris apterus as a blank matrix and by the determination of ecdysteroids in a single Drosophila larva. The lower limit of quantifications for the four target ecdysteroids (20-hydroxyecdysone, ecdysone, makisterone A, and 2-deoxyecdysone) were 0.01; 0.1; 0.05; and 0.025 pg·ml-1 (20; 200; 100; 50 fmol ml-1), respectively, with very good accuracy, precision (expressed as relative standard deviation <15%) and recoveries (96%-119.9%). The application potential of the new method was demonstrated by quantification of ecdysteroids in various biological materials including human serum.
Keywords: kapalinová chromatografie-hmotnostní spektrometrie; Ecdysteroids; quantification; submilligram sample amount; arthropods; human body fluid; ecdysteroid hormones; ekdysteroidy; Chromatography, High Pressure Liquid; dietary supplementation; vysokoúčinná kapalinová chromatografie; Hemolymph; hemolymfa; zvířata; Liquid Chromatography-Mass Spectrometry; Tandem Mass Spectrometry; ultratrace HPLC-MS analysis; larva; Larva; tandemová hmotnostní spektrometrie; Animals